2009
DOI: 10.1002/pbc.22011
|View full text |Cite
|
Sign up to set email alerts
|

Novel splice site mutations in the gamma glutamyl carboxylase gene in a child with congenital combined deficiency of the vitamin K‐dependent coagulation factors (VKCFD)

Abstract: Congenital combined deficiency of the vitamin K-dependent coagulation factors is a rare bleeding disorder caused by either a defect in the gamma-glutamyl carboxylase or the vitamin K epoxide reductase enzyme complex. The diagnosis should be considered when vitamin-K dependent factor activities are decreased and liver dysfunction, vitamin K deficiency, and factitious coumarin ingestion have been excluded. We report a case of VKCFD in a child resulting from compound heterozygosity for two novel splice site mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…One exception is a 14 bp deletion in intron 1, which is supposed to be involved in the protein expression [13]. VKCFD type 1 has been shown to result from compound heterozygosity of missense mutations in the GGCX gene [19,25-27]. VKOR was identified 34 years ago [28] but its biochemistry has been difficult to understand because of refractoriness to purification.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…One exception is a 14 bp deletion in intron 1, which is supposed to be involved in the protein expression [13]. VKCFD type 1 has been shown to result from compound heterozygosity of missense mutations in the GGCX gene [19,25-27]. VKOR was identified 34 years ago [28] but its biochemistry has been difficult to understand because of refractoriness to purification.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…The disease was coined VK-dependent clotting factor deficiency-1 (VKCFD1, OMIM#277450), an autosomal recessive disorder, characterized by a mild to severe bleeding tendency and a moderate predisposition to thrombotic events [13,20]. VKCFD1 was shown to be associated with skeletal (midfacial hypoplasia, reduced bone mass, chondrodysplasia punctata) or cardiac abnormalities (patent ductus arteriosus Botalli, septal closure defects) in some patients [13,21,22,23,24,25,26,27,28,29,30]. Next to VKCFD1, a second autosomal recessive coagulation factor deficiency exists, VKCFD2 (OMIM#607473), caused by VKORC1 (vitamin K epoxide reductase complex, subunit 1; OMIM*608547) mutations and is also characterized by a deficiency of all VK-dependent clotting factors.…”
Section: Introductionmentioning
confidence: 99%
“…A very similar VKCFD patient phenotype is also reported for GGCX mutations leading to type 1 deficiency. In some VKCFD1 patients, a phenotype similar to warfarin embryopathy is additionally found that includes facial hypoplasia and epiphyseal stippling, similar to a chondrodysplasia puncta phenotype, and also a pseudoxanthoma elasticum-like phenotype (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). These additional non-bleeding phenotypes are not common for VKCFD2 patients.…”
Section: Diagnosismentioning
confidence: 99%
“…Individuals that are heterozygous for VKORC1 : p.Arg98Trp normally develop no phenotype and exhibit activities for the VKD coagulation factors in normal range. In contrast, there are many more mutations in the GGCX gene reported to cause VKCFD1 in heterozygous, homozygous as well as compound heterozygous form (currently 27 mutations known) (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation